Sterculia diversifolia bears anti-cancer and immunomodulatory activities - Rabbi, Fazle; Zada, Amir; Adhikari, Achyut; Jabeen, Almas; Nisar, Amna; Ullah, Irfan (Bangladesh Journal of Pharmacology, 2017)
The present study was aimed to evaluate the methanolic extract and subsequent solvents soluble fractions of Sterculia diversifolia bark for cytotoxic, anti-cancer and immunomodulatory activities. Phytochemical investigation confirmed the presence of alkaloids, flavonoids, saponins, glycosides, etc. In the cytotoxic activity, n-hexane showed potent activity (LD50: 7.0 µg/mL) followed by dichloromethane fraction (LD50: 16.2 µg/mL). In the anti-cancer activity, dichloromethane fraction showed potent activity (IC50: 5.9 µg/mL) followed by ethyl acetate fraction (IC50: 9.5 µg/mL). While in the immunomodulatory assay, ethyl acetate fraction showed a very significant activity (IC50: 21.0 µg/mL) followed by dicloromethane and n-butanol fractions (IC50: 25.0 and 25.3 µg/mL respectively). Hence, it is clear that S. diversifolia has anti-cancer and immunomodulatory agents. Video Clip of Methodology: ROS Assay: 2 min 9 sec Full Screen Alternate